Listening and appreciation - Green, Lucy (Music, Informal Learning and the School: A New Classroom Pedagogy, 2008)
Few subjects in the school curriculum, and indeed few activities in our lives, accord primary importance to listening as a skill. Probably of all curriculum subjects, the study of foreign languages is most similar to music education in its attention to listening skills. But even in language studies, as in music education, the components of the curriculum which involve some reading or writing have normally been accorded the highest status, and carry a great deal of weight in assessment practices. Music is an invisible entity, and its invisibility gives us difficulties when we try to apply names to its component parts. This is particularly so in the absence of any form of writing or notation through which we can externalize music and make it visible. Not only is music itself invisible, but its invisibility makes music listening skills particularly elusive. Music education has developed a sophisticated set of criteria and practices for assessing performance. Many of these are, in general terms, internationally, though not universally, recognized by musicians and music educators across all levels and many styles (Green 2000 has a fuller discussion of this). However, the assessment of music listening is generally much less developed. It has tended to rely on requiring learners to produce some kind of account of what is going on inside their heads while they listen. Such accounts can range from general descriptions of the music, to naming specific properties or relationships within it, to taking down music by dictation. All in all, it is hard both to enhance and to assess music listening through education, other than as an offshoot of other activities.